A REFLECTION OF ACCOUNTABILITY AND TRANSPARENCY ON THE APPLICATION OF SHURA IN ISLAMIC SOCIAL FINANCE INITIATIVES - Nurulhuda Abd Rahman; Khairul ‘Ayuni Mohd Kharuddin; Mohd Isa Mohd Deni (Journal of Islamic, Social, Economics and Development, 2024)
The Islamic social finance (ISF) ecosystem involves diverse stakeholders and implementation partners, each pursuing different objectives and bounded by different challenges. Such collaboration can optimise the strengths of these various parties and help resolve conflicts. Nevertheless, effective collaboration could be hindered by obstacles such as regulatory restrictions, as well as constraints on resources and expertise. Shura is a mutual consultation between parties in a decision-making process. By incorporating the shura approach, the management of ISF initiatives can foster accountability and transparency in all transactions. This article discusses the reflection of accountability and transparency through the application of shura in ISF initiatives by way of inclusive decision-making, shared responsibility, ethical oversight, Islamic values integration, long-term vision, as well as adaptiveness and responsiveness. A framework is proposed for the application of shura in a sustainable ISF ecosystem under the oversight of His Royal Highness Sultan, Bank Negara Malaysia, and in alignment with the broader socio-economic goals and values of the country.